Differential function of Themis CABIT domains during T cell development. - Toshiyuki Okada; Takeshi Nitta; Kentaro Kaji; Akiko Takashima; Hiroyo Oda; Norimasa Tamehiro; Motohito Goto; Tadashi Okamura; Michael S Patrick; Harumi Suzuki (PLoS ONE)
Themis (also named Gasp) is a newly identified Grb2-binding protein that is essential for thymocyte positive selection. Despite the possible involvement of Themis in TCR-mediated signal transduction, its function remains unresolved and controversial. Themis contains two functionally uncharacterized regions called CABIT (cysteine-containing, all-β in Themis) domains, a nuclear localization signal (NLS), and a proline-rich sequence (PRS). To elucidate the role of these motifs in Themis's function in vivo, we established a series of mutant Themis transgenic mice on a Themis(-/-) background. Deletion of the highly conserved Core motif of CABIT1 or CABIT2 (Core1 or Core2, respectively), the NLS, or the PRS abolished Grb2-association, as well as TCR-dependent tyrosine-phosphorylation and the ability to induce positive selection in the thymus. The NLS and Core1 motifs were required for the nuclear localization of Themis, whereas Core2 and PRS were not. Furthermore, expression of ΔCore1- but not ΔCore2-Themis conferred dominant negative-type inhibition on T cell development. Collectively, our current results indicate that PRS, NLS, CABIT1, and CABIT2 are all required for positive selection, and that each of the CABIT domains exerts distinct functions during positive selection.